Bio-inspired Asymmetric Design and Building of Biomimetic Smart Single Nanochannels - Hou, Xu (Springer Theses, Recognizing Outstanding Ph.D. Research, 2013)
In this thesis, the author introduces various bio-inspired smart nanochannel systems. A strategy for design and preparation of novel artificial responsive symmetric/asymmetric single nanochannel systems under various symmetric/asymmetric stimuli is presented for the first time. The author's research work utilizes ion track etching polymer nanochannels with different shapes as examples to demonstrate the feasibility of the design strategy for building novel artificial functional nanochannels using various symmetric/asymmetric physicochemical modifications. The development of these nanochannels and their potential applications is a burgeoning new area of research, and a number of exciting breakthroughs may be anticipated in the near future from the concepts and results reported in this thesis. Research into artificial functional nanochannels continues to drive new developments of various real-world applications, such as biosensors, energy conversion systems and nanofluidic devices. The work in this thesis has led to more than 15 publications in high-profile journals.